Student perspectives on mental health support and services in the UK. Issue 4 (20th April 2020) - Batchelor, Rachel; Pitman, Emma; Sharpington, Alex; Stock, Melissa; Cage, Eilidh
ABSTRACT: Student mental health is an issue of growing concern. Past research indicates that many students are not accessing the support they require, which may in part be due to issues surrounding the standards of the available services. Using a participatory framework, the current study utilised a mixed-methods design to examine student experiences of National Health Service (NHS) mental health services and perspectives of peer support. An online survey was completed by 376 UK students to examine their experiences of NHS mental health services, as well as their attitudes towards peer support. Several improvements were identified for future NHS mental health services regarding reduced waiting times, better access to alternative treatments and facilitating more patient-centred communication. Benefits of peer support services were also noted, including the potential to normalise experiences and promote belonging. These findings have implications for understanding how we can best support students experiencing mental health difficulties.